2012
DOI: 10.1111/j.2047-3095.2012.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses' Perceived Use of NANDA‐I Nursing Diagnoses in the Community Setting

Abstract: Use of NANDA-I nursing diagnoses should be encouraged among community health nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The low scoring of the PHNs on documentation of care using the Muller‐Staub checklist at pretest supported the findings of Ogunfowokan et al. () that PHNs in Nigeria are not using the SNLs for client care in the community setting. This poor documentation among the PHNs is reflected in the lack of documentation of client care using NANDA‐I nursing diagnoses, nursing outcomes, and nursing interventions.…”
Section: Discussion Of Findingssupporting
confidence: 70%
“…The low scoring of the PHNs on documentation of care using the Muller‐Staub checklist at pretest supported the findings of Ogunfowokan et al. () that PHNs in Nigeria are not using the SNLs for client care in the community setting. This poor documentation among the PHNs is reflected in the lack of documentation of client care using NANDA‐I nursing diagnoses, nursing outcomes, and nursing interventions.…”
Section: Discussion Of Findingssupporting
confidence: 70%
“…A self‐administered questionnaire was used in this study and included the following parts: Demographical data including information about the academic progress. Perceptions toward NANDA‐I Nursing Diagnosis scale. This is a component of a questionnaire developed in a previous study (Ogunfowokan et al., ) to assess the knowledge of using NANDA‐I nursing diagnosis in the community nursing courses. The researchers in that study reviewed the literature on NANDA‐I nursing diagnosis and retrieved questions from the concept of nursing diagnosis, which seemed congruent to the common misconception of nursing students.…”
Section: Instrumentsmentioning
confidence: 99%
“…Five out of the 13 statements were negative statements. Cronbach's alpha coefficient for the questionnaire was obtained from a previous study to show high internal consistency at 0.77 (Ogunfowokan et al., ). Positions on Nursing Diagnosis (POND) scale, which was developed to measure the attitudes of nurses toward the idea of nursing diagnosis (Lunney & Krenz, ). The POND scale is a 20‐item scale used in the semantic differential technique of the words to measure and encourage the expression of people's attitudes toward NANDA nursing diagnosis.…”
Section: Instrumentsmentioning
confidence: 99%
“…Attempts are being made by nurses in some clinical areas to use SNTs in the development of care plans. However, empirical studies on SNTs in Nigeria are few and show poor knowledge and limited use in clinical as well as in community settings (Ogunfowokan et al., ; Olaogun, Ogini, Oyedeji, Nnahiwe, & Olatubi, ; Sani & Sani, ). Furthermore, while several studies in developed countries have reported the benefit of EHRs (Cheung, Mayhew, Weir, & Grimshaw, ; Welch et al., ; Zhang, Yu, & Shen, ), empirical information on the use of standardized nursing care plans (SNCPs) in EHRs from a developing nation is limited.…”
mentioning
confidence: 99%